Analisis Beban Kerja Perawat Dengan Menggunakan Metode Daily Log Di Instalasi Rawat Darurat RSU DDR. Soetomo Surabaya - Danding Koes Indriati, - (2011)
One of the nursing care qualities relies on the balance of the working quantities and load of nursing work in a hospital. The load of nursing work can be seen from their duties based on major duties, additional duties, the quantity of patient being cared, composition of working capacity due to educational background and also daily duty with time of shift that were scheduled. This study was aimed to analyze the load of nursing work by using daily log methods and were using explorative descriptive as methods of research. The population was all nurses that work in emergency unit in RS DR. Soetomo Surabaya, with samples picked by using purposive sampling technique. Respondents were 33 nurses from 3 different shift, choosen by using inclusion and exclusion criteria. Instrument used in this research was forms of Nursing work that were separated in productive and non productive nursing activities. The result of this study indicate that were 331 minutes or 5 hours and 30 minutes time spent for productive nursing activities in the morning shift (about 79% from all total time in a shift), it means morning shift was in a light medium work load. In evening shift there was 350 minutes or 5 hour and 49 minutes (83 ,3% from total time in a shift) spent for productive nursing activities, means evening shift were in medium work load. Night shift was spent 404,73 minutes or abut 6 hour and 44 minutes for productive activities. Nurses work load can be concluded were in normal work load ranged light to medium, and neither in hard work load. It's very important to nursing manager emergency unit to evaluate nursing work load eventually, to see how hard was nurse's duties as well. To make working load balance on every duty, the number of nurse on morning duty can be transfer into evening or night shift in order to decreade work load on those shift. This suggest can be done to equal the spare of the duties, so nurse can give patient more comprehent and good nursing care.